Pelatihan Public Speaking Bagi Tokoh Agama Di Desa Sanrobone Kabupaten Takalar - Nur Setiawati; Bisyri Abdul Karim; Hasmirati (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2021)
This Community Service and preaching (PkMD) activity through Public Speaking Training for Religious Leaders in Sanrobone Village, Takalar Regency aims to develop self-potential and improve persuasive communication skills for religious leaders in Sanrobone village. The development and improvement of persuasive communication skills is very much needed for religious leaders and religious instructors to balance the impact and influence of globalization and advances in science and technology. This condition has an impact on changes in the orientation and behavior of the community and especially the younger generation in Sanrobone who prefers a hedonistic and individualistic lifestyle and abandons religious teachings and local cultural values. Therefore, it is necessary to immediately make systematic efforts, among others, by improving communication skills with the wider community through Public Speaking Training for Religious Leaders in Sanrobone village, Takalar regency. The results of this training will later help the trainees to increase their self-confidence and self-development facilities, convey ideas systematically and coherently so that participants are able to lead meetings, sessions and discussions while defending their opinions well. Besides that, participants are also expected to be able to make public speeches while at the same time increasing their authority and self-image. In the end, participants will gain the trust of the community and can influence the community in delivering messages and public services properly